A Systematic Review of Key Factors Influencing Farmers' Economic Well-Being in the Rice Supply Chain - Normasari, Nur Mayke Eka; Hartanto, Angela Kirana; Sakti, Fikri Amori; Lekatompessy, Gregor Dalton Maranatha; Septiangga, Ibnu Jourga; -, Kevin; Febriani, Maria; Rahman, Muhammad Alif; Rachmadani, Muthi Amelia (Institut Teknologi Dirgantara Adisutjipto, 2025)
The economic well-being of farmers in Indonesia's rice supply chain is influenced by multiple structural and systemic challenges. This study conducts a systematic literature review (SLR) by analyzing 56 articles from 10 different countries published in the last six years to identify key factors impacting farmers' financial resilience and sustainability. Findings highlight significant price volatility, limited market access, high production costs, and dependency on intermediaries, which collectively hinder economic stability. Additional challenges include inadequate government support, technological gaps, climate-related risks, and inefficiencies in supply chain management. Addressing these issues requires integrated policy interventions, improved infrastructure, and cooperative strategies to enhance farmers' livelihoods and promote a more equitable rice supply chain.